Interaksi Aktor Kebijakan dalam Pengelolaan Wilayah Jembatan Suramadu dalam Perspektif Advocacy Coalition Framework (ACF) - Tamrin, M. Husni (Universitas Muhammadiyah Sidoarjo, 2017)
This study aimed to describe the phenomena in concerning policy actors interaction involved in development of Surabaya Suramadu Bridge Surface Area (KKJSS) as well as the factors that influence the policy changes in KKJSS development with some of the variables and indicators in the Advocacy Coalition Framework (ACF). This research used qualitative method with case study research strategy. Based on the research result, it can be concluded that the interaction of actors that occurred in the development of KKJSS formed a advocacy coalition of policy actors in maintaining and accommodating their interests, Surabaya City Government as policy actors seeks to share core belief policy and coordinate with Central Government so as to be able to convince that the management of KKJSS can still be managed by the Surabaya City Government without the presence of BPWS. Another case with the coalition formed on the BPWS, BPWS coalition with the Government of East Java Province which is only limited to the central government representative in the region and also become one of the steering committee of BPWS but the coalition can not be maximized.